Parent Care by Indian and Belgian Caregivers in their Roles of Daughter/Daughter-in-Law - Prishnee Datta, Ype H. Poortinga and Alfons Marcoen (Journal of Cross-Cultural Psychology 2003; 34; 736, 2003)
Patterns of scores on measures of the strength of current caregiver/care receiver relationship quality (adult attachment, closeness, and conflict) and measures of parent care (filial concern, caregiver burden, and amount of parent care given) were examined in India and Belgium (Flanders) with middle-aged women looking after their mother and/or mother-in-law. Patterns of scores in care receivers'ratings of current bonds with their daughters and daughters-in-lawwere also investigated. The results suggested that the relationship between daughter-in-lawand mother-in-lawis relatively less close in India than in Belgium. In contrast, patterns of variables related to actual behavior follow cultural prescriptions, with Indian daughters-in-law providing more care for their Mothers-in-law. It is concluded that cultural demands will determine actual behavior but have, at most, a limited influence when it comes to deep-rooted interpersonal relations, such as the attachment between mother and daughter.